Hubungan motivasi dan self-efficacy dengan tindakan pencegahan pengendalian infeksi perawat di ruang rawat inap rumah sakit: Relationship between motivation and self-efficacy with nurses' infection control prevention actions in hospital inpatient areas - Khaerunisa Priwardani; Tatiana Siregar (Poltekkes Kemenkes Jayapura, 2025)
Healthcare-Associated Infections (HAIs) are among the major global health problems that significantly impact the quality of hospital services. Nurses play a vital role in implementing infection prevention and control (IPC) measures. This study aimed to examine the relationship between motivation and self-efficacy with nurses' IPC practices in hospital inpatient settings. A cross-sectional design with a quantitative approach was employed, involving 135 nurses from the inpatient wards of RSUD X Jakarta, who were selected through purposive sampling. Research instruments included a motivation questionnaire based on Herzberg's theory, the General Self-Efficacy Scale (GSES), and the IPC questionnaire developed by the Indonesian Ministry of Health (2017). Unadjusted analysis showed that motivation (p < 0.001; OR = 4.98; 95% CI: 2.37–10.45) and self-efficacy (p < 0.001; OR = 12.25; 95% CI: 5.43–27.62) were significantly associated with nurses' IPC practices in inpatient care. In addition, gender was also associated with IPC actions to a considerable extent (p = 0.028; OR = 0.36; 95% CI: 0.14–0.91). However, in the adjusted analysis using multivariate logistic regression, only self-efficacy (p < 0.001; OR = 9.00; 95% CI: 3.80–21.31) was found to influence the implementation of IPC significantly. Self-efficacy demonstrated a more decisive influence than motivation on nurses' IPC practices. Efforts to enhance self-efficacy should be integrated into hospital training programs and policies to improve the quality of care and patient safety.